Analisis Faktor-Faktor yang Mempengaruhi Permintaan Agrowisata Stroberi di Kecamatan Berastagi Kabupaten Karo - Sinaga, Anggiat; Zendrato, Melvin (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Strawberry agro-tourism in Berastagi is one of the tourist destinations that offers a unique experience in the form of strawberry picking activities directly from the garden and consumption of fresh strawberries by enjoying the beauty of the surrounding natural scenery. However, consumer interest in buying strawberries is still relatively low, so the development of strawberry agro-tourism is a solution to increase strawberry consumption in the region. This study aims to analyze the factors that influence the demand for strawberry agritourism in Berastagi. The variables studied include travel costs, income per month, travel time to tourist sites, and gender dummies. The research method used is multiple linear regression analysis using primary data collected through interviews with purposively selected tourists. The results showed that income and travel costs have a positive and significant effect on the demand for strawberry agro-tourism, while travel time to tourist sites has a negative and significant effect. The gender variable has no significant effect on demand. These findings indicate that to increase public interest in strawberry agritourism, it is necessary to develop promotional strategies and improve accessibility to tourist sites. Thus, the potential of strawberry agro-tourism can be maximized to support increased strawberry consumption and strengthen the tourism sector